Consumer Informatics: - Boyer, C.; Section Editor for the IMIA Yearbook Section on Consumer Informatics (Yearbook of Medical Informatics, 2011)
To explore how the Internet is being used as a source of information, but also as a source of consumption in certain health-related fields. Determine the negative and positive impacts of this trend, depending on the topic or quality standards of websites.Synopsis of the articles selected for the IMIA Yearbook 2011.Six papers from international peer reviewed journals have been selected for the section on health information systems.The articles selected discuss issues of major concern for online health information seekers, because of their positive or negative impact on health outputs.
Keywords: Consumer informatics; online health information; e-Health; quality; ethics